Effect of Bio-Fertilizers Azotobacter Chroococcum and Pseudomonas Fluorescens on Growth of Broccoli (Brassica Oleracea L. Var. Italica) - Salim, Hussein Ali (JOURNAL OF ADVANCES IN BIOLOGY, 2018)
A field experiment was carried out at the experimental farm of soil laboratory belong to Directorate of Diyala Agriculture, Iraq during 2017. The experiment comprises of different doses of biofertilizers (Azotobacter chroococcum and Pseudomonas fluorescens) 0.08, 0.14 and 0.28 g/plant to assess their performance on growth characteristics of broccoli. The experiment was laid out in randomized complete block design having four treatments with three replications. The data analysis revealed that the maximum of leaves numbers in the treatment of Biofertilizer, 0.28 (23.4) whereas the maximum area of bigger leaf and head diameter was recorded in all treatments of Biofertilizer 0.08, 0.14 and 0.28 (415.9, 340.3 and 373.9 cm) and (15.5,15.4 and 15.1cm) as compared with control (108.8 cm) and (3.0 cm) respectively.